Stability of Black Garlic Extract on Various pH and Temperature - Yudhayanti, Putu Eka; Permana, I Dewa Gde Mayun; Nocianitri, Komang Ayu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 7 No 1 (2020): Scientific Journal of Food Technology (March), 2020)
Black garlic is a garlic that experiences warming at a certain temperature and time to find higher antioxidant activity. This research aimed to know effect of antioxidant content’s stability of extract BG to pH and temperature. The experimental design used in this research was a completely randomized design with replication, which consisted of two factors. The first factor was pH (4, 6 and 8). The second factor was temperature (30, 50 and 70ºC). Data were analyzed with analysis of variance, followed by Duncan test. The results showed that pH and processing temperature very influential to antioxidant activity, total phenolic and total flavonoid. The results showed that the best treatment was pH 4 and temperature 30ºC which the best resulted antioxidant activity, total phenolic and total flavonoid that stablest. The resulted of antioxidant activity, stability of total phenolic and total flavonoid that were 75,13%, 42,47% and 77,71%. The treatment of pH and processing temperature change compounds of extract black garlic. Myricetin and quercetin appeared on treatment pH 4 with temperature 30ºC and pH 8 with temperature 70 ºC. The treatment of pH and processing temperature of black garlic extract reduced antioxidant activity, total phenol and total flavonoid. pH and temperature form new compounds.